Blockchain: A Possible Alternative to Achieving Health Information Exchange (HIE) (International Journal of Innovative Research in Computer Science & Technology, 2020)
A patient may have access to one or more  healthcare organizations, meaning that their health  information is spread across separate EHR systems,  resulting in data fragmentation. Thus, the medical history of  a patient may not be complete, consistent or comprehensive  if the records cannot be combined into a single consistent  overview that may not be efficient for the future diagnosis  of the patient. Health Information Exchange (HIE) relates to  the electronic transfer of health care information between  institutions and practitioners within a specific group, region  or hospital. However, HIE is surrounded with various  challenges such as data insecurity, threat to patient privacy,  dependency on third parties and so on. Blockchain through  its characteristics such as safety, privacy, decentralization,  and immutability has the ability to transform health care,  putting the patient at the core of the health care ecosystem,  and enhancing health data security, privacy, and  interoperability thereby offering HIE with excellent  potential. In this paper Health Information Exchange (HIE)  and Blockchain Technology are discussed and the  possibility of using blockchain technology to achieve HIE is  presented.
Keywords: Health Information Exchange; Blockchain Technology; Health care; Interoperability; Security